Water collection by the body in a viperid snake, Bothrops moojeni - Andrade, D. V.; Abe, Augusto Shinya [UNESP] (Brill Academic Publishers, 2000)
We describe a previously unreported behavior for water collection in juveniles of a neotropical viperid snake. Bothrops moojeni. When sprayed over, this snake displays a stereotyped coiling, bringing its body loops in close contact with each other, so that water is retained between the loops and over the body surface. This water is continuously ingested during and after its collection. The functional significance of the water collecting behavior is suggested to be related with the acquisition of water from short rainfalls, and with the special climatic and geologic conditions of B. moojeni habitat. Rates of evaporative water loss did not differ between juvenile and adult snakes, but since juveniles have a greater surface-to-volume ratio, they were significantly more sensitive to desiccation than the adults.